2015
DOI: 10.1007/s13277-015-3213-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 promotes cell proliferation in human hepatocellular carcinoma partly by targeting HEPN1

Abstract: It has been reported that miR-21 is upregulated in hepatocellular carcinoma (HCC), and overexpressed miR-21 plays a key role in promoting cell cycle progression, reducing cell death and favoring angiogenesis and invasion. Overexpression of hepatocellular carcinoma, downregulated 1 (HEPN1) exhibits an antiproliferative effect on HepG2 cells, suggesting that silencing of HEPN1 may contribute to carcinogenesis of hepatocytes. In silico analysis revealed that HEPN1 may be a potential target of miR-21. Using quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The HEPN1 gene is another target of miR-21, and its silence induced by miR-21 significantly accelerated the tumor growth of HCC. In addition, mitogen-activated protein kinase-kinase 3 (MAP2K3), reversion-inducing-cysteine-rich protein with kazal motifs (RECK), and programmed cell death 4 (PDCD4) were the direct targets of miR-21, and their expression and functions were notably suppressed in HCC (41,43,44).…”
Section: Downregulation Of Mirnas In Hccmentioning
confidence: 99%
“…The HEPN1 gene is another target of miR-21, and its silence induced by miR-21 significantly accelerated the tumor growth of HCC. In addition, mitogen-activated protein kinase-kinase 3 (MAP2K3), reversion-inducing-cysteine-rich protein with kazal motifs (RECK), and programmed cell death 4 (PDCD4) were the direct targets of miR-21, and their expression and functions were notably suppressed in HCC (41,43,44).…”
Section: Downregulation Of Mirnas In Hccmentioning
confidence: 99%
“…Numerous miRNAs were identified from thousands of cancer related studies serving as promising biomarkers or therapeutic targets (15,16). For instance, miR-21, miR-124, miR-148a and miR-384 have been reported to be involved in the progression of HCC (17)(18)(19)(20). In recent years, emerging studies showed that aberrant expression of long noncoding RNAs (lncRNAs), a class of ncRNAs more than 200 nucleotides in length, was involved in the tumorigenesis and development of various cancer, including HCC (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Several miRNAs have been identified to play a critical role in regulating HCC tumorigenesis and metastasis signaling networks [2528]. Elucidating the underlying mechanisms of miRNA in liver carcinogenesis may improve diagnostic and therapeutic strategies for HCC.…”
Section: Discussionmentioning
confidence: 99%